Rousseau on Language and Writing Two Perspectives. - Stocker, Barry; Bolender, John. (Luton : Andrews UK, 2014)
Two contemporary philosophers take two very different approaches to Jean-Jacques Rousseau's Essay on the Origin of Languages, and then each reflects upon the approach of the other. Barry Stocker takes a deconstructionist approach, discussing the importance of Rousseau in the work of Jacques Derrida. John Bolender approaches Rousseau's Essay in terms of cognitive science, most especially in light of the theories of Noam Chomsky and Alan Page Fiske. Both authors agree that Rousseau's Essay sti...
Cover; Contents; Front matter; Title page; Publisher Information; Foreword, Lance Kirby; Body matter; Emotion in Language, John Bolender; Rousseau and Derrida on Liberty and on Language, the First Social Institution, Barry Stocker; Reply to "Rousseau and Derrida on Liberty and on Language, the First Social Institution", John Bolender; Reply to "Emotion in Language", Barry Stocker; Back matter; References
Description based upon print version of record.
Includes bibliographical references.
Description based on print version record.
Keywords: Philosophy, French; Philosophy; Rousseau, Jean-Jacques, -- 1712-1778.; French philosophy -- Rousseau, Jean-Jacques, 1712-1778.; Philosophy; Rousseau, Jean-Jacques, -- 1712-1778.; PHILOSOPHY / Essays; PHILOSOPHY / Reference; PHILOSOPHY / History & Surveys / Modern; Electronic books; Electronic books